Teachers' Perceptions of Inclusive Education and its Implication for Adult Education in the Bahamas - Norrisa Newton; Janelle Carbridg; Yvonne Hunter-Johnson (Adult Education Research Conference, 2014)
Despite the paradigm shift globally regarding the adoption of inclusive education, teachers still have varying preconceive misconceptions about its successful implementation and practices in the general education classroom. This study focused on teachers' perception of adapting inclusive education policies and procedures in the Bahamas and its implication for adult education.